Examining the Equilibrium Relationships between Foreign Direct Investment Inflows and Employment in Manufacturing and Services Sectors: Evidence from Malaysia - Bekhet, Hussain Ali (Journal of Social and Development Sciences, 2013)
The current paper examines the long-run and short-run equilibrium relationships between FDI inflows and employment in Malaysian manufacturing and services sectors using ARDL approach for the 19722011 period. It employs ADF and PP tests to detect the stationary levels of above variables. Also, it utilizes the bounds F-statistics test to identify the co-integration among variables. Results of ARDL approach indicate the presence of significant long-run and short-run equilibrium relationships between FDI inflows and employment in manufacturing and services sectors. The paper’s findings are of particular interest and importance to Malaysian policy makers towards increasing FDI inflows and employment in manufacturing and services sectors.